A facile doxorubicin-dichloroacetate conjugate nanomedicine with high drug loading for safe drug delivery - Yang CL (Dove Medical Press, 2018)
Conglian Yang,1 Tingting Wu,1 Yuting Qin,1 Yan Qi,1 Yu Sun,1 Miao Kong,1 Xue Jiang,1 Xianya Qin,1 Yaqi Shen,2 Zhiping Zhang1,3,4 1Tongji School of Pharmacy, 2Department of Radiology, Tongji Hospital, Tongji Medical College, 3National Engineering Research Center for Nanomedicine, 4Hubei Engineering Research Center for Novel Drug Delivery System, Huazhong University of Science and Technology, Wuhan, People’s Republic of China Background: Doxorubicin (DOX) is an effective chemotherapeutic agent but severe side effects limit its clinical application. Nanoformulations can reduce the toxicity while still have various limitations, such as complexity, low drug loading capability and excipient related concerns. Methods: An amphiphilic conjugate, doxorubicin-dichloroacetate, was synthesized and the corresponding nanoparticles were prepared. The in vitro cytotoxicity and intracellular uptake, in vivo imaging, antitumor effects and systemic toxicities of nanoparticles were carried out to evaluate the therapeutic efficiency of tumor.Results: Doxorubicin-dichloroacetate conjugate can self-assemble into nanoparticles with small amount of DSPE-PEG2000, leading to high drug loading (71.8%, w/w) and diminished excipient associated concerns. The nanoparticles exhibited invisible systemic toxicity and high maximum tolerated dose of 75 mg DOX equiv./kg, which was 15-fold higher than that of free DOX. It also showed good tumor targeting capability and enhanced antitumor efficacy in murine melanoma model. Conclusion: This work provides a promising strategy to simplify the drug preparation process, increase drug loading content, reduce systemic toxicity as well as enhance antitumor efficiency. Keywords: self-assembly, doxorubicin, drug delivery, chemotherapy, nanomedicine